Competition law and the Malaysian financial market - Abdul Rahman, Nasarudin; Ahamat, Haniff; Abd Ghadas, Zuhairah Ariff (The International Association of IT Lawyers, 2014)
The Objective of competition law and financial regulation is to ensure a well-functioning market. While competition law and financial regulation share the same goal, the manner in which they pursue this objective is different. Unlike competition law, which solely focuses on competition, financial regulation pursues other goals such as financial stability, reliability of payment system and consumer protection. This paper seeks to study the interplay between financial regulation and competition law from the Malaysian perspective. While the new Competition Act 2010 applies to financial sector, some powers to oversee competition issues are also reserved for the financial regulator. This may result in two possibilities: (i) financial regulation and competition law complement each other (ii) a possible conflict of responsibility between the financial regulator and the competition authority, which requires an effective cooperation and coordination.